Role for Retinoic Acid-Related Orphan Receptor Alpha (RORα) Expressing Macrophages in Diet-Induced Obesity - Hams, Emily; Roberts, Joseph; Bermingham, Rachel; Hogan, Andrew E.; O'Shea, Donal; O'Neill, Luke; Fallon, Padraic G. (Frontiers in Immunology, 2020)
The transcription factor ROR plays an important role in regulating circadian rhythm, inflammation, metabolism and cellular development. Herein we show a role for ROR-expressing macrophages in the adipose tissue in altering the metabolic state of mice on a high-fat diet. The expression of Rora and RORA is elevated in white adipose tissue from obese mice and humans when compared to lean counterparts. When fed a high-fat diet Rora reporter mice revealed increased expression of Rora-YFP in macrophages in white adipose tissue deposits. To further define the potential role for Rora-expressing macrophages in the generation of an aberrant metabolic state Rorafl/flLysMCre/+ mice, which do not express Rora in myeloid cells, were maintained on a high-fat diet and metabolic parameters assessed. These mice had significantly impaired weight gain and improved metabolic parameters in comparison to Rorafl/fl control mice. Further analysis of the immune cell populations within white adipose tissue deposits demonstrates a decrease in inflammatory adipose tissue macrophages (ATM). In obese reporter mouse there was increased in Rora-YFP expressing ATM in adipose tissue. Analysis of peritoneal macrophage populations demonstrates that within the peritoneal cavity Rora-expression is limited to myeloid-derived macrophages, suggesting a novel role for ROR in macrophage development and activation, which can impact on metabolism and inflammation.